The Influence of The Audit Commitee, Audit Opinion and Auditor Switching on Firm Value - Syamsuri; Suripto; Purba, Sofyan Helmi (Universitas Pamulang, 2025)
This study aims to analyze the influence of independent variables, namely audit committee, audit opinion and auditor turnover on the dependent variable, namely Company Value for property and real estate sector companies in 2019-2023 listed on the Indonesia Stock Exchange (IDX) and related company websites from secondary data taken from financial reports that have been audited by a Public Accounting Firm in the form of an Independent Auditor Report, The population was taken from 85 companies, while according to the criteria it produced 15 companies with a purpose sample method with data analysis using multiple regression analysis with data management using eviews 12. The results of the study showed that simultaneously the audit committee variable, audit opinion variable and auditor turnover variable had an effect on the company value variable. for the audit committee variable did not affect the company value variable, the audit opinion variable affected the company value variable and the auditor turnover variable did not affect the company value variable.